Factory Farming and Ocean Degradation: Coopetitive Strategies for the Environment - CARFI’, David; DONATO, Alessia (Journal of Mathematical Economics and Finance; Vol 7 No 1 (2021): JMEF, Volume VII, Issue 1(12), Summer 2021, 2021)
In this study, we propose possible coopetitive strategies between countries in order to reduce environmental problems related to the meat production. In particular, the problem of factory farming and ocean degradation is studied. We propose a coopetitive strategy focused in investments promoting and suggesting the change of diet (reformulating food products towards a healthy diet based on vegetables) and improving the sustainability of production practices (production of plant-based food and reduction of the associated emissions). We create a mathematical model of interaction between two players and we completely study the associated game, suggesting a possible compromise solution.